2019
DOI: 10.1111/are.14216
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of liposome‐encapsulated interferon alpha (IFN‐α) vaccine and anti‐grass carp reovirus effect

Abstract: This study was to develop liposome‐encapsulated interferon alpha (IFN‐α) vaccine and to evaluate the immune response of IFN‐α vaccine to grass carp reovirus (GCRV) infection. After IFN‐α vaccine was constructed and administrated to grass carps through intraperitoneal injection, the expressions of immune‐related genes such as IFN‐α, interferon regulatory factor 1 (IRF1), signal transducers and activators of transcription 3 (STAT3) and myxovirus resistant (Mx) genes in the liver, kidney, spleen and intestine of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The same trends are observed in propolis liposomes, which powerfully enhanced the cytotoxic effect on Hep-2 cells compared with the unencapsulated ones [26]. Because of the phospholipid membrane, liposome possesses characteristics of great biocompatibility and low toxicity [13]. Sun et al [11] reported that the Caco-2 cells treated with anthocyanins-loaded nanoliposomes had lower cell viability compared with unencapsulated anthocyanins at the same concentration.…”
Section: Cell Viabilitymentioning
confidence: 72%
“…The same trends are observed in propolis liposomes, which powerfully enhanced the cytotoxic effect on Hep-2 cells compared with the unencapsulated ones [26]. Because of the phospholipid membrane, liposome possesses characteristics of great biocompatibility and low toxicity [13]. Sun et al [11] reported that the Caco-2 cells treated with anthocyanins-loaded nanoliposomes had lower cell viability compared with unencapsulated anthocyanins at the same concentration.…”
Section: Cell Viabilitymentioning
confidence: 72%